2021
DOI: 10.1186/s12864-021-07481-w
|View full text |Cite
|
Sign up to set email alerts
|

Pi-starvation induced transcriptional changes in barley revealed by a comprehensive RNA-Seq and degradome analyses

Abstract: Background Small RNAs (sRNAs) are 20–30 nt regulatory elements which are responsible for plant development regulation and participate in many plant stress responses. Insufficient inorganic phosphate (Pi) concentration triggers plant responses to balance the internal Pi level. Results In this study, we describe Pi-starvation-responsive small RNAs and transcriptome changes in barley (Hordeum vulgare L.) using Next-Generation Sequencing (NGS) RNA-Seq … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…In many plant species, several studies have shown that the majority of DEGs identified in K-starved plants are linked to phytohormones (especially auxin and jasmonate), cation transporters (especially iron, zinc, and Ca transporters), Ca signaling, and protein phosphorylation [ 33 , 34 , 35 , 36 , 37 ]. Concerning transcriptomic analysis of P-starved plants, a study performed on wheat identified several DEGs associated with plant defense, plant stress responses, nutrient mobilization, or pathways involved in the gathering and recycling of phosphorus [ 38 ]. In another study authors reported that among the 1644 DEGs in roots of P-deprived plants, most of them belonged to pathways involving phosphorylated metabolites such as nucleic acids and phospholipids [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many plant species, several studies have shown that the majority of DEGs identified in K-starved plants are linked to phytohormones (especially auxin and jasmonate), cation transporters (especially iron, zinc, and Ca transporters), Ca signaling, and protein phosphorylation [ 33 , 34 , 35 , 36 , 37 ]. Concerning transcriptomic analysis of P-starved plants, a study performed on wheat identified several DEGs associated with plant defense, plant stress responses, nutrient mobilization, or pathways involved in the gathering and recycling of phosphorus [ 38 ]. In another study authors reported that among the 1644 DEGs in roots of P-deprived plants, most of them belonged to pathways involving phosphorylated metabolites such as nucleic acids and phospholipids [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…AtSgpp expression is responsive to abiotic stresses, with inorganic phosphate (Pi) starvation causing one of the largest inductions of expression (Caparrós‐Martín et al ., 2013). In wider studies of HAD genes, they have been found to be upregulated in response to Pi stress (Sega et al ., 2021) and contain a high frequency of Pi responsive cis elements in their promoters (Du et al ., 2021). The physiological function of AtSGPP is thought to be housekeeping detoxification, modulation of sugar‐phosphate balance and Pi homeostasis (Caparrós‐Martín et al ., 2013; He et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate (Pi) is the most important mineral element delivered by AMF to the host plant. Previous studies have shown that miR399 responds to stress induced by low phosphorus in monocot and dicot plants ( Fujii et al., 2005 ; Bari et al., 2006 ; Chiou et al., 2006 ; Du et al., 2018 ; Sega et al., 2021 ). The results suggest that miR399 may be involved in AMS regulation by balancing Pi uptake pathways.…”
Section: Discussionmentioning
confidence: 99%